The Idea of The Right To Recall Constituents’ Vs The Principle Of Secrecy In The Election Law: The Death Of The Right of Constituents In Positive Law - Novelino, Romadu; Hoesein, Zainal Arifin (Dinasti Research, 2025)
This article examines the paradox of democracy in the Indonesian electoral system through the conflict between the right of recall by constituents and the principle of secrecy regulated in the Election Law. Normatively, the principle of secrecy is intended to protect the political freedom of voters from pressure and intimidation. However, in practice, this principle has lost its substantive meaning when people's political choices become public consumption and are even used as a tool for political transactions. At the same time, the people as constituents do not have the constitutional right to withdraw the mandate against the people's representatives who are not trustworthy, because the power of recall is entirely in the hands of political parties. This study uses a juridical-normative approach with conceptual analysis and case studies to examine the principle of secrecy that is no longer appropriate in the legislative election system and the mechanism of recall of the principle of people's sovereignty as stipulated in Article 1 paragraph (2) of the 1945 Constitution. Using the perspective of legal positivism, this study found a gap between the formal legality of the electoral system and the morality of democratic justice. The positivization of election law that places the party as the owner of the people's representative seat has shifted the sovereignty of the people to the sovereignty of the party. The results of the study show that the death of constituent sovereignty is the result of political party dominance over the representation mechanism and weak protection of people's political rights after the election. The right of recall should be returned to the people (constituents) as the owners of the legitimate political mandate through a constituency-based recall (people's recall right/constituency recall) with the mechanism of 1) recall petition; 2) public ethics and fact testing by independent institutions; and 3) political parties cannot reject or hinder the submission of recall if they have met the constitutional and administrative requirements. Political parties should only play a role, as facilitators, not executors.